Die verband tussen lees- en spelvermoë en akademiese prestasie by Graad 5- tot 7-leerders - Bann, Chantal (University of the Free State, 2013)
The purpose of the study was to determine the relationship between the reading- and spelling ability and academic performance of grade 5 to 7 learners. Non-experimental research with a correlational design was followed. The research group consisted of 282 Afrikaans boys and girls in grades 5 to 7. The participants' reading- and spelling abilities were measured by using the ESSI Reading and Spelling Test. For an indication of the learners' academic performance, the learner’s average performance in Afrikaans, English and Mathematics over the past three terms was obtained. It was found that there is a significant positive correlation between reading and spelling ability and academic achievements of grade 5 to 7 learners. Therefore, it can be concluded that the better the learner’s reading and spelling ability, the better the student will tend to perform academically, and vice versa.

Die doel van die studie is om die verband tussen lees- en spelvermoë en akademiese prestasies van graad 5- tot 7-leerders vas te stel. Nie-eksperimentele navorsing, met 'n korrelasionele ontwerp is hier gevolg. Die ondersoekgroep het bestaan uit 282 Afrikaanssprekende seuns en dogters in graad 5 tot 7. Die deelnemers se lees- en spelvermoë is deur middel van die ESSI Lees- en Speltoets bepaal. Om 'n aanduiding van die leerders se akademiese prestasie te verkry, is hulle gemiddelde persentasies vir Afrikaans, Engels en Wiskunde oor die afgelope drie kwartale gebruik. Daar is bevind dat daar 'n beduidende positiewe verband tussen lees- en spelvermoë en akademiese prestasie van graad 5- tot 7-leerders bestaan. Die gevolgtrekking kan dus gemaak word dat hoe beter die leerder se lees- en spelvermoëns is, hoe beter die leerder geneig sal wees om op akademiese gebied te presteer, en andersom.
Dissertation (M.A. (Psychology))--University of the Free State, 2013
Article 1 of 2. Article 2: http://hdl.handle.net/11660/2279
Keywords: Academic achievement -- Forecasting; Reading -- Ability testing; Spelling ability; Reading (Elementary) -- South Africa; Education, Elementary -- South Africa; Literacy -- Study and teaching (Elementary) -- South Africa; Reading comprehension; Decoding; Encoding; Phonological awareness; Phonetic awareness; Morphology